2006
DOI: 10.1111/j.1349-7006.2006.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of cholesterol 7α‐hydroxylase (CYP7A1) and colorectal adenomas: Self Defense Forces Health Study

Abstract: Bile acids have long been implicated in colorectal carcinogenesis, but epidemiological evidence is limited. Cholesterol 7α α α α-hydroxylase (CYP7A1) is the rate-limiting enzyme producing bile acids from cholesterol. A recent case-control study showed a decreased risk of proximal colon cancer associated with the CC genotype of the CYP7A1 A-203C polymorphism. The present study examined the relationship between the CYP7A1 A-203C polymorphism and colorectal adenoma, which is a well-established precursor lesion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
(37 reference statements)
2
10
0
Order By: Relevance
“…, adenoma characteristics, age, and sex). Our results corroborate the findings of Tabata et al , (28) and Hagiwara et al , (27) who reported an association between the CYP7A1 promoter variant and risk of CRA and CRC, respectively. Collectively, these results strengthen the link between genetic variation in CYP7A1 and CRC risk and provide additional support favoring the role of bile acid metabolism in the biology of colorectal carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…, adenoma characteristics, age, and sex). Our results corroborate the findings of Tabata et al , (28) and Hagiwara et al , (27) who reported an association between the CYP7A1 promoter variant and risk of CRA and CRC, respectively. Collectively, these results strengthen the link between genetic variation in CYP7A1 and CRC risk and provide additional support favoring the role of bile acid metabolism in the biology of colorectal carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Further, the uniqueness of the sample set, which includes only polyp formers, limits the generalizability of our results. Despite these limitations, the overall findings show consistency with biological mechanisms ( CYP7A1 variation as a determinant of bile acid levels and CYP7A1 gene regulation as a putative UDCA target) and, more importantly, replicate prior associations between genetic variation in CYP7A1 and risk of CRA development (27, 28). …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Cholecystectomy, which changes the profile of bile acids, has been generally associated with risk of proximal colon cancer, 40 and polymorphisms in the cholesterol 7α-hydroxylase (CYP7A1), the rate limiting enzyme producing bile acids from cholesterol, have been associated with risk of proximal colon cancer and adenoma. 41,42 Although not entirely consistently observed, in some studies associations with hyperinsulinemia or the metabolic syndrome have been observed only for proximal colon cancer or adenoma, 43,44 or the associations were stronger in the proximal colon. 45,46 Future studies of obesity and weight change should examine potential subsite differences.…”
Section: Discussionmentioning
confidence: 98%
“…Ercc2 encodes an ATP-dependent 5'-3' helicase that participates in the opening of the damaged DNA after the damage recognition step in nucleotide excision repair [5,9]. Cyp7a1 is the ratelimiting enzyme that converts cholesterol into cholesterol 7α-hydroxycholesterol in the first step of the classical pathway of bile acid synthesis [47]. Cdkn1a is a major downstream target of p53 and responsible for exerting G1 arrest after DNA is damaged [18].…”
Section: Discussionmentioning
confidence: 99%